Peripheral and central auditory dysfunction, cardiometabolic multimorbidity, and cognitive performance in community-dwelling older adults: a cross-sectional study - Ruan, Jian; Hu, Xiuhua; Zhang, Min; Zhang, Weibin; Zhang, Yan; Han, Zhao; Chen, Jie; Ruan, Qingwei; He, Jingchun; Chen, Bing; Bao, Zhijun (Frontiers in Neuroscience, 2026)
ObjectivesBoth age-related peripheral or central hearing loss, and cardiometabolic multimorbidity (CMM), which are independent association with global and domain-specific cognitive impairment, are common among older adults. Cardiometabolic diseases also are independent risk factors of age-related hearing loss. The first aim of the study was to investigate the independent and joint influence of CMM and low- and high-frequency hearing loss or central auditory processing dysfunction (CAPD) on global and domain-specific cognitive impairment. The second aim was to investigate whether CMM mediate the effects of age-related hearing loss on cognitive performance.MethodsIn total, 508 eligible community-dwelling dementia-free older adult participants agreed to participate and completed a cross-sectional investigation. The averages of thresholds at 0.5, 1, and 2 kHz for low frequency (LPTA) and at 4, 6, and 8 kHz for high frequency (HPTA) were calculated. CAPD was assessed using SNR (signal-to-noise ratio threshold) in a words-in-noise test. Global and domain-specific cognitive performance was measured using a comprehensive neuropsychological test battery. This study analyzed the independent associations between LPTA, HPTA, CAPD, or CMM and global and domain-specific cognitive performance after adjusting for each other and other confounders. Weighted logistic regression were used to assess the joint effects of CMM and the LPTA, HPTA, or CAPD on cognitive performance. The R package “Mediation” was used to examine whether CMM mediated the associations between LPTA, HPTA, or CAPD and cognitive performance.ResultsCMM was independently associated with global cognitive performance in pre-MCI [β (95% CI): 0.124 (0.047, 0.202), adjusted p = 0.0068], MCI groups [0.131 (0.055, 0.206), adjusted p = 0.068] for total sample, and the sensitivity test (adjusted p = 0.0506, and 0.012, respectively) after adjusted for all confounders. CMM in Model 2 was also significantly associated with executive function in the sensitivity test (β, 0.087; 95% CI, 0.028, 0.145; adjusted p = 0.035). The SNR value and global cognition in Model 2 was significantly associated between the cognitively normal group and the MCI group (adjusted p = 0.044 in total sample, and p = 0.051 in sensitivity test). HPTA in Model 2 remained independently associated with attention/executive function in the sensitivity test (β, 0.005; 95% CI, 0.001, 0.008; adjusted p = 0.0395). The dose–response relationships between the LPTA, HPTA, or SNR and CMM on global cognition were most significant in the cognitively normal group than in the MCI group. The significant joint effect of CMM and HPTA on executive function also been observed. In the sensitivity test, the indirect mediation effect of HPTA on global cognitive performance in the MCI group vs. the cognitively normal group after adjustments for all confounders through CMM were significant. Approximately 16.172% of the total effect of HPTA on global cognition was explained by the mediation effect through CMM.ConclusionCMM and CAPD were significantly associated with global cognition. CMM and HPTA were significantly associated executive function in the sensitivity test. CMM, and LPTA, HPTA, or CAPD had jointly effects on global cognition. CMM and HPTA had significant joint effect on executive function. CMM might mediate the association between the HPTA and global or executive function in individuals with LPTA ≤ 40 dB HL. These findings indicated that an integrated interventional approach for presbycusis and CMM simultaneously may delay cognitive decline in older adults.